Structure Analysis Of Graphene Micro Oxide From Old Coconut Shell Waste - Rika Nanda; - Ramli (PILLAR OF PHYSICS, 2022)
Synthesis of graphene oxide from old coconut shell waste material. It has many applications, one of which is used as a microwave absorber. Old coconut shells are used as waste because the ingredients are easy to get. This study aims to analyze the microstructure of graphene oxide from old coconut shell waste. In the carbonization process using a furnace with temperature variations from 250˚C to 450˚C, the furnace time is 120 minutes. Making activated charcoal from old coconut shells using the modified hummers method with oxidizing agents KmnO2, H2SO4, and NaNO3. Characterization of graphene oxide from old coconut shell waste using FTIR, XRD and SEM. The test results using FTIR on GO samples show the formation of GO material where the sample contains functional groups containing bonds between carbon (C), Hydrogen (H) and Oxygen (O), the highest crystal size on XRD is 43.20800529 nm, and particle size the best SEM was obtained at GO 250˚C with a particle size of 65.701671 nm where the larger the particle size, the larger the surface pores of the sample, so that the better microwave absorbent was produced.